IS ENVIRONMENTAL ALIGNMENT AND BUSINESS PERFORMANCE: A CONCEPTUAL APPROACH - Garg, K.; Joubert, R.J.O.; Pellissier, R. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This paper proposes a conceptual model termed "IS environmental alignment" that focuses on the support provided by IS strategy to minimize the gap between perceived environmental uncertainty and realized/objective environmental conditions. The model uses the Chan et al [9] alignment measurement method to measure IS strategic alignment as it provides a quantitative measure. In due course the proposed model would be tested in industry and would examine the affect of IS environmental alignment on business performance. The implication of the model lies in the effective use of deployed IS systems by organizations. AFRIKAANSE OPSOMMING: ’n Konsepmodel word voorgel